In vitro reproduction in the annual pasture legumes subterranean clover (Trifolium subterraneum L.) and French serradella (Ornithopus sativus Brot.) - Castello, M.; Stefanova, Katia; Nichols, P.; Nutt, B.; Revell, C.; Croser, J. (Blackwell Publishing, 2016)
© 2016 John Wiley & Sons Ltd. Pasture legumes are important components of both mixed farming rotations and permanent pastures in temperate climates. Breeding of two widely sown pasture legumes, subterranean clover (Trifolium subterraneum L.) and French serradella (Ornithopus sativus Brot.), is constrained by the long generation cycle, typically enabling only one generation per year. We hypothesized manipulation of culture medium and conditions would enable the development of a laboratory-based protocol for in vitro reproduction in subterranean clover and French serradella. In vitro flowering and viable seed set was induced from both species. For subterranean clover, the most effective treatment was culturing on modified MS medium with 1 µm kinetin and 0·1 m sucrose under a 100 µmol m-2 s-1 light intensity and continuous photoperiod. For French serradella, culture on a hormone-free B5 medium with 5 mm NH4Cl and 0·1 m sucrose under a 100 µmol m-2 s-1 light intensity and 20 h photoperiod was optimum. It is expected this technique will have application in accelerating generation turnover within breeding programs, for the study of factors influencing flowering in pasture legumes, and for the propagation of valuable yet enfeebled plants such as embryo-rescued hybrids.